Biosorption Potential of Hydrilla (Hydrilla verticillata) on Nickel. - Gopez, Apple Ann S. 4 0 16; 5 (2005)
u
Thesis (B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2